Effectiveness of Interactive Learning Media Based on Articulate Storyline in Increasing the Ability to Understand the Concept of a Healthy Home in Children with Cerebral Palsy - Septrika Puspita Sari; Nurhastuti Nurhastuti; Mega Iswari; Ardisal Ardisal; Antoni Tsaputra (Universitas Muhammadiyah Enrekang, 2024)
This research was motivated by problems that occurred in one cerebral palsy student who was not yet able to understand the concept of a healthy home in class VIII. To overcome this, researchers aim to improve the ability to recognize the concept of a healthy home in children with cerebral palsy by using articulate storyline based interactive learning media. This type of research is experimental research using a quantitative approach in the form of Single Subject Research (SSR) with A-B-A design. Variable X in this research is interactive learning media based on an articulate storyline, while variable Y in this research is the ability to recognize the concept of a healthy home. The data collection techniques used are observation, tests and documentation. The data collection tool in this research is a test instrument in the form of a checklist. Data analysis was carried out using visual analysis methods. The research results showed that there was an increase in the ability to recognize the concept of a healthy home in children with cerebral palsy by using articulate storyline-based interactive learning media. This is proven by condition A1, during 3 meetings the child obtained a score of 45.4%, 45.4%, 45.4%. Condition B during 7 meetings the child obtained a score of 51.5%, 63.6%, 66.6%, 87.6%, 100%, 100%, 100%. Then, in condition A2 for 3 meetings the child obtained a score of 96.9%, 96.6%, 96.6%. After analysis, articulate storyline based interactive learning media was proven to be able to increase the ability to recognize the concept of a healthy home in children with cerebral palsy.